Formulasi sediaan pasta daging lidah buaya (Aloe vera (L.)Burm.f.) dan uji aktivitas antibakteri terhadap bakteri Streptococcus mutans - Meutia, Cut; Dalimunthe , Gabena Indrayani; Lubis , Minda Sari; Yuniarti , Rafita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Introduction: Aloe vera (Aloe vera (L.) Burm.f.) is a plant that contains 95% water. The rest is in the form of other active ingredients (essential oils, amino acids, minerals, vitamins, enzymes, and glycoproteins). The type of aloe vera used to make herbal aloe vera is the Barbadensis type, which contains substances for human needs, such as Vitamins A, B1, B2, B6, B12, Vitamin E, and Vitamin C. This plant can also cure diabetes, heart disease, and other diseases. Aloe vera can be formulated into toothpaste preparations because it can improve hygiene and reduce plaque in the mouth. Objective: This study aimed to make a new formulation of (aloe vera (L.) Burm.f.) as a toothpaste preparation and evaluate its antibacterial activity against Streptococcus mutans bacteria. Methods: This study uses an experimental method. In this study, aloe vera was formulated as toothpaste. The physical evaluation carried out included tests for water content, total ash content, water-soluble extract content, ethanol-soluble extract content, acid-insoluble extract content, organoleptic test, oh test, homogeneity test, spreadability test, adhesion test, test viscosity, and foam formation test. Results: Based on the research results, it can be seen that aloe vera flesh has antibacterial activity against Streptococcus mutans bacteria. Conclusion: This research concludes to make a new formulation of (aloe vera (L.) Burm.f.) as a toothpaste preparation and evaluate its antibacterial activity against Streptococcus mutans bacteria.